Theoretical and practical aspects of the knowledge examination test modeling - Karaliūnaitė, Julija; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2016)
In the article one knowledge examination test for which is applied known mathematical model is considered. It is shown how the characteristic functions of the questions of the text can be constructed and how there may be made predictions about the results of the test made of the analyzed questions. Also the perspectives of the further research are presented.